Idiopathic bilateral adrenal haemorrhage related to acute adrenal insufficiency. (31st May 2013) - Ogino, Jun; Toda, Joe; Onitsuka, Shiro; Hashimoto, Naotake
Abstract : A 54-year-old woman presented with sudden epigastralgia and left back pain. She had no significant history. Laboratory data showed mild inflammation and no liver or renal dysfunction. Abdominal CT showed left adrenal enlargement and haemorrhage. Hydrocortisone therapy was started to prevent adrenal insufficiency before laboratory findings for ACTH (adrenocorticotropic hormone) and cortisol levels. On the second hospital day, abdominal CT showed additional right adrenal enlargement and haemorrhage. The serum cortisol level suggested adrenal insufficiency. No specific findings were detected by bilateral adrenal angiography. 6 to 12 months later, abdominal CT showed decreased bilateral adrenal haemorrhage. This case illustrates the importance of prompt diagnosis and treatment of acute adrenal insufficiency, and shows sequential changes in the size of bilateral adrenal haemorrhage. Rapid corticosteroid replacement is important if acute adrenal insufficiency is suspected. In a case with unilateral adrenal haemorrhage, the possibility of additional adrenal haemorrhage on the opposite side should also be considered.